Çimento Fabrikalarında Makina Performansına Dayalı Bakım Planlaması Sistemi Ve Yönetimi - Öztürk, Ümit (Fen Bilimleri Enstitüsü, 1998)
Günümüz modern teknoloji çağı olarak bilinmektedir. Gelişen bu teknoloji beraberinde hızla artan rekabetide getirmiştir. Artan hızlı nüfus sebebiyle ihtiyaçlarda artmış, bunu karşılayabilmek için üretim miktarıda ihtiyaç oranında artmıştır. Ayrıca artan hızlı nüfus sebebiyle yeni yerleşim yerleri, yeni kurulacak sanayi bölgeleri, iş merkezleri vs. gerekmektedir. Tüm bunların kurulması için gerekli temel malzeme lerin başında çimento gelmektedir. Çimento fabrikaları 24 saat sürekli üretim yapan büyük endüstriyel tesislerdir. Bu fab rikalarda makina arızası ve dolayısıyla üretim kaybı hiç istenmez. Bununla birlikte, çimento sanayi belirli özellikleri olan bir üretim alanıdır. Bunlar ; ü Çok problemli bir üretim koludur. q Çok sayıda ve çok çeşitli makina teçhizatının biraraya gelmesinden oluşmaktadır. Dolayısı ile bu konuda karşılaşılan problemlerde o nispette çok ve özellikle çeşitli olmaktadır. q Hammaddesi taş ve toprağa dayalı bir sanayidir. Böyle olunca malzemenizde 99 elementin 99 'ununda bulunması ihtimali mevcut olmaktadır ve birkaç ana elementin dışında ürününüze ne etkiler getireceğini bilmeniz mümkün değildir. Bu etkiler her fabrikada izahı güç problemlerin ortaya çıkması sonucunu doğurmaktadır. Çözümlerinde ise, uygulama seviyesinde mevcut olması normal olmayan özel bilgi ve donanım gereklidir. Bu da ancak bir mütehassıs araştırma - geliştirme biriminin oluşturulmasıyla sağlanabilir. q Yeni ve daha verimli teknolojilere daha çok ihtiyaç duyan bir sanayi koludur. Tüm bu sebepler yüzünden uygulanan bakım tekniği, verimliliği doğrudan etkileyen bir faktör olacaktır. Bu tezde en modern bakım yöntemi olarak bilinen makina performansına dayalı bakım planlaması ve uygulamalarından sözedilecek, yöntemin klasik bakım yöntemlerine göre avantajlarına değinilecek, çimento fabrikalarının çalışma prensibi ile ürün eldesini doğrudan etkileyen kritik makinaların bir sınıflandırması yapılarak, makina perfor mansına dayalı bakım tekniğinin bu kritik makinalar arasından seçilen 10 makina üzerinde uygulanması incelenecektir. Periyodik titreşim ölçümleri ile makinaların performanslarının sürekli izlenmesi arasındaki farklara değinilecek, periyodik ölçümlere dayalı performans izleme yönteminden sürekli izleme yöntemine geçiş için yapılması gereken fizibilite çalışmasına yer verilecektir. Elde edilen sonuçların değerlendirilmesiyle tez sonuçlandırılacaktır.

Our century is known as "the modern technology period". This developed technology has resulted in ever increasing competition between companies. Requirements have increased due to the increased population and production quantity has also increased by the rate of this requirement. Besides, due to the fast increased population, it is necessary to build new housing places, new industry regions etc. Cement is listed at the head of the necessary main materials to establish all these requirements. Cement plants are large industrial facilities producing continuously 24 hours. At these factories failure of machinery and loss of production can never be afforded. The cement industry is a production area with its own specialities. These are ; a) It is a production branch which has many problems, b) Production includes various machinery, c) The raw materials are obtained from stone and soil. Therefore, there is a probability that all of 99 elements are in your material. So one can't know which elements affect the production except a few main elements. These affects cause sophisticated problems. Specialized knowledge is necessary to solve these problems. This can only be provided by an expert research-development unit, d) It is a industry branch which needs new and more advanced production techno logies. Due to these reasons, applied maintenance technology will be a factor which effects directly the productivity. The subjects which will be covered in this thesis is summarised below ; - Importance of maintenance techniques and failure mechanisms, - Classical maintenance systems, - Working principles of cement factories, - Critical machines which effect the production, - Maintenance planning system depending on machine performance, - Advantages of the maintenance planning system. Xll A computer-based vibration system consists of an integrated hardware and software package which uses a host computer workstation for data storage and diagnostic analysis. This system also includes a portable data collector and vibration transducer. The transducer is responsible for accurately converting mechanical vibration into an anolog electrical signal in terms of phase, frequency, and amplitude. The portable data collector temporarily stores incoming vibration signals from the transducer and processes the waveforms using Fast Fourier Transform (FFT) techniques. The data collector is capable of performing a variety of machinery measurements as either a routine survey instrument or a general purpose signal analyzer. It is designed for use so a great degree of skill is not required. A technician follows memory loaded measurement routes to the appropriate locations on the machine, attaches the transducer, and starts the measurement by pressing a single button. A typical data collector has the storage capacity for hundreds of measurement points, logging for each overall vibration level, waveform data, FFT data and additional trend or analysis parameters. Some data collectors can be used as a stand-alone analyzer capable of functioning as an ossiloscope. The data collectors also allow the user to monitor instantaneous changes in FFT signature, time waveform, synchronous peak and phase, overall vibration level, machine RPM, pressure, thickness and current. Data collectors also may perform multi-plane, multi-speed balancing using a downloadable balancing program. A few data collectors can perform advanced diagnostic functions such as synchronous time averaging, peak-hold averaging, triggered data capture, coast down, and start up capture (Bode and Nyquist display). The heart of the PC-based vibration programs is the analysis software which executes on the host computer such as a portable PC. The analysis software allows for ; 1. Creation of a machine database containing information for each machine or part to be monitored, and the path or route to take in monitoring. 2. Definition of data analysis parameters that allows for more flexibility in selecting the vibration analysis method to be used on individual machine parts. 3. Exchange of database route programs and machine data with the portable collector (downloading and uploading). 4. Scanning of data for exceptional values which may indicate machine part deficiencies or problems, and verification of the health of each machine. 5. Generation of graphical displays for ease of vibration analysis and communication with management or other interested parties. 6. Compliation of data in a historical manner for trending and archiving, and allowing for justification of program continuance. Xlll Once data has been dumped into the host computer, the PC-based PDM programs provide four important vibration analysis methods in which to evaluate health of the equipment ; 1. A trained engineer using the analysis software performs vibration signature analysis on equipment. A working knowledge of vibration analysis is essential for this method. 2. The analysis software has built-in and changeable automatic problem detectors that warn which equipment 's vibration levels are beginning to exceed industry or individual companies recommended standarts. 3. The analysis software also has built-in trending capabilities to automatically warn which equipment is showing continued increases in vibration levels. The parameters used to capture these levels may be changed to fit each equipment 's characteristics. 4. The analysis software has an automated expert system capability to diagnose problems. The expert knowledge bases are built from the combined knowledge of some of the most prominent analysts in the industry. - Advantages of the maintenance planning system are ; 1. Increased equipment availability resulting in greater return on invested capital by maximizing the running time between machine overhauls. This is one of maintenance planning system 's most important benefits since vibration analysis allows for the identification of problem equipment and also confirms which equipment does not need any scheduled maintenance. 2. Reduced maintenance costs and increased productivity by reducing the probability of catastrophic failure. Actually, studies show that maintenance planning programs have virtually eliminated surprise failures in some plants. This would be of particular importance to industries that carry their equipment to a job site. Studies also show that typical emergency repair costs for catastrophic failures average 10 times the cost of planned repairs. 3. More efficient repairs because repair quality can be checked and guaranteed. Studies show that approximately 10 percent of new parts pulled off the shelf have defects or flaws. These defects can cause the replaced component to fail, and also may result in latent damage to other machine parts. It is beneficial to check the quality of newly purchased and recently replaced parts. 4. Reduced inventory cost by reducing spare part inventory. Some plants which have started successful maintenance planning programs have been able to turn 'backup' production lines into profitable ones. The main production lines showed a significant reduction in downtime to deem a backup line unnecessary. XIV 5. Improved operator and public safety because condition monitoring gives adequate lead time to enable machines to be repaired before reaching a critical condition. This is of particular importance to industries such as hospitals, where the health of the patients is directly dependent upon the quality of the hospitals diagnostic and life-sustaining equipment. 6. More efficient negotiations with equipment vendors regarding the purchase and repair of equipment. Maintenance planning programs evaluate the health of new equipment and give substantial advantages in negotiating with vendors on any repairs or redesigns that might be required. Analysis Of Vibration All rotating machinery generate vibration, the analysis of which renders valuable information about the condition of the machines. This article describes the type of vibration signals to be expected for faults in typical elements. Low Frequency Range Frequency Spectra obtained from measurements made on the motor bearings or gearbox bearings will reveal low frequency components at shaft revolution speed originating from unbalance, misalignments, bent shaft etc. At the second harmonic, i.e. twice the rotation speed, components originating from bent shaft and misalignments will also be found. In other words, by comparing the change in these components with time the appearance of such faults can be detected and diagnosed. The major problem with journal bearings is hydrodynamic instability in the system consisting of shaft / oil film / bearing housing. Oil whirl is a self - excited vibration, where the center of gravity of the shaft moves around within the clearance of the bearing at sub-synchronous speed. It arises typically at lightly loaded high speed shafts, and at frequencies between 42 % and 47 % of rotational speed. It seems to depend on the surface of the shaft and bearing. A last type of fault appearing in this low frequency area is mechanical looseness. In many cases machanical looseness will create interharmonic and subharmonic components, i.e. a "half harmonic, a "one-and-a-half harmonic, a "two-and-a-half harmonic etc. Medium Frequency Range Higher up in the frequency range, components originating from the toothmesh in the gearbox will be found and are referred to as medium frequency components. XV They will be at frequency corresponding to rotational speed multiplied by the number of teeth on the gear, and referred to as the toothmeshing frequency. When the gearbox wears, the gear profile will gradually change due to sliding between two teeth in mesh at any point except at the pitch point. This indicates that changes due to wear in a gearbox will turn up at the second harmonic of toothmeshing frequency and, since the change is not sinusoidal, higher harmonics will be revealed as well. At incipient local fault, on the other hand, will not increase the level at toothmesh frequencies and its harmonics. Imagine a cracked tooth which is not yet broken, and will consequently not be noticed by the operation personnel. As the fault spreads out in the gearbox to cover several defective teeth, the signal will change character from the pulse-like one just described to one which has more energy and which looks more like an amplitude modulated signal. And it has high amplitude sidebands around toothmeshing frequencies and its harmonics, spaced at rotational speed. High Frequency Range An incipient fault in a rolling-element bearing will typically be a crack or corrosion pit either on the inner race, on the outher race, or on the rolling element itself. This crack will create small impulses every time one of the rolling-elements passes over it. These impulses will transmit energy to the bearing housing, which in turn will vibrate at its natural frequency (resonance frequency). So we are able to detect an incipient fault in a rolling-element bearing by monitoring the level of vibration filtered around one of the resonance frequencies of the mechanical structure. These pulses have far less energy than the low frequency and medium frequency signals, and must therefore be detected at high frequencies.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Bakım planlama sistemi; Makineler; Performans; Çimento fabrikaları; Maintenance planning system; Machinery; Performance; Cement factories